Microvascular maturation by mesenchymal stem cells in vitro improves blood perfusion in implanted tissue constructs. (January 2021) - Atlas, Yoann; Gorin, Caroline; Novais, Anita; Marchand, Marion F.; Chatzopoulou, Eirini; Lesieur, Julie; Bascetin, Rumeyza; Binet-Moussy, Clément; Sadoine, Jeremy; Lesage, Matthieu; Opsal-Vital, Sibylle; Péault, Bruno; et al.
Abstract: Blood perfusion of grafted tissue constructs is a hindrance to the success of stem cell-based therapies by limiting cell survival and tissue regeneration. Implantation of a pre-vascularized network engineered in vitro has thus emerged as a promising strategy for promoting blood supply deep into the construct, relying on inosculation with the host vasculature. We aimed to fabricate in vitro tissue constructs with mature microvascular networks, displaying perivascular recruitment and basement membrane, taking advantage of the angiogenic properties of dental pulp stem cells and self-assembly of endothelial cells into capillaries. Using digital scanned light-sheet microscopy, we characterized the generation of dense microvascular networks in collagen hydrogels and established parameters for quantification of perivascular recruitment. We also performed original time-lapse analysis of stem cell recruitment. These experiments demonstrated that perivascular recruitment of dental pulp stem cells is driven by PDGF-BB. Recruited stem cells participated in deposition of vascular basement membrane and vessel maturation. Mature microvascular networks thus generated were then compared to those lacking perivascular coverage generated using stem cell conditioned medium. Implantation in athymic nude mice demonstrated that in vitro maturation of microvascular networks improved blood perfusion and cell survival within the construct. Taken together, these data demonstrate the strong potential of in vitro production of mature microvasculature for improving cell-based therapies. Graphical abstract: Image 1